PTPN2 phosphatase deletion in T cells promotes anti‐tumour immunity and CAR T‐cell efficacy in solid tumours. (5th December 2019) - Wiede, Florian; Lu, Kun‐Hui; Du, Xin; Liang, Shuwei; Hochheiser, Katharina; Dodd, Garron T; Goh, Pei K; Kearney, Conor; Meyran, Deborah; Beavis, Paul A; Henderson, Melissa A; Park, Simone L; et al.
Abstract: Although adoptive T‐cell therapy has shown remarkable clinical efficacy in haematological malignancies, its success in combating solid tumours has been limited. Here, we report that PTPN2 deletion in T cells enhances cancer immunosurveillance and the efficacy of adoptively transferred tumour‐specific T cells. T‐cell‐specific PTPN2 deficiency prevented tumours forming in aged mice heterozygous for the tumour suppressor p53. Adoptive transfer of PTPN2‐deficient CD8 + T cells markedly repressed tumour formation in mice bearing mammary tumours. Moreover, PTPN2 deletion in T cells expressing a chimeric antigen receptor (CAR) specific for the oncoprotein HER‐2 increased the activation of the Src family kinase LCK and cytokine‐induced STAT‐5 signalling, thereby enhancing both CAR T‐cell activation and homing to CXCL9/10‐expressing tumours to eradicate HER‐2 + mammary tumours in vivo . Our findings define PTPN2 as a target for bolstering T‐cell‐mediated anti‐tumour immunity and CAR T‐cell therapy against solid tumours. Synopsis: This study reveals a role for protein tyrosine phosphatase N2 (PTPN2) in cancer immunosurveillance and T‐cell infiltration into solid tumours. Antagonizing PTPN2 thus represents a promising therapeutic strategy for adoptive T‐cell therapy. T‐cell‐specific PTPN2 deletion prevents tumour formation in p53 +/− mice without exacerbating inflammation. PTPN2 deletion enhances LCK‐mediated CAR T‐cell cytotoxicity. PTPN2 deletion promotes STAT5‐mediated CXCR3 expression and CAR T‐cell homing. PTPN2‐deficient CAR T cells eradicate solid tumours in vivo . PTPN2 inhibition enhances the activity of human CAR T cells. Abstract : Protein tyrosine phosphatase N2 inhibits tumour T‐cell infiltration and CAR T‐cell cytotoxicity and may thus be a therapeutic target to enhance solid‐tumour immunotherapy.